Management of Idiopathic Facial Palsy in Pediatric Patients: A Case Series - Parayash Dallakoti; Sunanda Sundas; Sagar Adhikari; Sumana Sulu; Amita Rai (Journal of South Asian Association of Pediatric Dentistry)
Background: Bell’s palsy, presently recognized as lower motor neuron palsy, is a diagnosis of elimination after careful exclusion of other etiologies. It tends to be the result of events that are compressive, infected, inflammatory, or traumatic to the nerve. The patient may present with signs of acute, idiopathic facial paralysis, sagging corners of the mouth, and an absence of the nasolabial fold on the impacted side. Case Description: This case series presents three different cases of Bell’s palsy treated with different treatment modalities such as systemic steroids and antiviral medications, methylcobalamin, home exercises, physiotherapy, and transcutaneous electrical nerve stimulation (TENS) therapy. Conclusion: Herpes simplex virus is the most frequent cause of Bell’s palsy; however, there are several additional etiologies for facial palsy that should be thoroughly ruled out. Bell’s palsy is less frequent in children as compared to adults; hence, early diagnosis and proper management are important.